A general copper-catalysed enantioconvergent radical Michaelis–Becker-type C(sp3)–P cross-coupling - Wang, Li-Lei; Zhou, Huan; Cao, Yu-Xi; Zhang, Chi; Ren, Yang-Qing; Li, Zhong-Liang; Gu, Qiang-Shuai; Liu, Xin-Yuan (Nature Synthesis, 2023)
The Michaelis–Becker reaction of H-phosphonates with alkyl halides represents an ideal means for synthesizing alkyl phosphorous compounds. However, the enantioconvergent conversion of racemic alkyl halides into α-chiral alkyl phosphorous compounds in this reaction is an insurmountable challenge because of the inherent SN2 mechanism. Here we disclose a copper-catalysed enantioconvergent radical Michaelis–Becker-type C(sp3)–P cross-coupling. Key to the success of this reaction is the use of multidentate chiral anionic ligands for enhancing the reducing capability of the copper catalyst to favour a stereoablative radical pathway over a stereospecific SN2-type process. Moreover, the ligand architecture is also able to assist the robust association of copper species with alkyl radicals over H-phosphonates, therefore exerting remarkable chemo- and enantioselectivity. This protocol covers a range of (hetero)benzyl-, propargyl- and α-aminocarbonyl alkyl bromides and chlorides. When allied with follow-up transformations, this method provides a versatile platform for valuable α-chiral alkyl phosphorous building blocks and drug leads.Copper-catalysed enantioconvergent radical Michaelis–Becker-type C(sp3)–P cross-coupling of diverse racemic alkyl halides with H-phosphonates has been achieved, overcoming the competing SN2 mechanism. Multidentate chiral ligands are crucial to prevent catalyst poisoning and enhance the reducing capability of the copper catalyst for initiation of the radical process.